A systematic review and network meta-analysis of the safety of early interventional treatments in rheumatoid arthritis. (19th July 2021) - Adas, Maryam A; Allen, Victoria B; Yates, Mark; Bechman, Katie; Clarke, Benjamin D; Russell, Mark D; Rutherford, Andrew I; Cope, Andrew P; Norton, Sam; Galloway, James B
Abstract: Objectives: To evaluate the safety of treatment strategies in patients with early RA. Methods: Systematic searches of MEDLINE, EMBASE and PubMed were conducted up to September 2020. Double-blind randomized controlled trials (RCTs) of licensed treatments conducted on completely naïve or MTX-naïve RA patients were included. Long-term extension studies, post-hoc and pooled analyses and RCTs with no comparator arm were excluded. Serious adverse events, serious infections and non-serious adverse events were extracted from all RCTs, and event rates in intervention and comparator arms were compared using meta-analysis and network meta-analysis (NMA). Results: From an initial search of 3423 studies, 20 were included, involving 9202 patients. From the meta-analysis, the pooled incidence rates per 1000 patient-years for serious adverse events were 69.8 (95% CI: 64.9, 74.8), serious infections 18.9 (95% CI: 16.2, 21.6) and non-serious adverse events 1048.2 (95% CI: 1027.5, 1068.9). NMA showed that serious adverse event rates were higher with biologic monotherapy than with MTX monotherapy, rate ratio 1.39 (95% CI: 1.12, 1.73). Biologic monotherapy rates were higher than those for MTX and steroid therapy, rate ratio 3.22 (95% CI: 1.47, 7.07). Biologic monotherapy had a higher adverse event rate than biologic combination therapy, rate ratio 1.26 (95% CI: 1.02, 1.54). NMA showed no significant difference between strategies with respect to serious infections and non-serious adverse events rates. Conclusion: The study revealed the different risk profiles for various early RA treatment strategies. Observed differences were overall small, and in contrast to the findings of established RA studies, steroid-based regimens did not emerge as more harmful.